Isolation and Phylogenetic Analysis of Novel Viruses Infecting the Phytoplankton Phaeocystis globosa (Prymnesiophyceae) - Brussaard, C. P. D. (American Society for Microbiology, 2004)
Viruses infecting the harmful bloom-causing alga Phaeocystis globosa (Prymnesiophyceae) were readily isolated from Dutch coastal waters (southern North Sea) in 2000 and 2001. Our data show a large increase in the abundance of putative P. globosa viruses during blooms of P. globosa, suggesting that viruses are an important source of mortality for this alga. In order to examine genetic relatedness among viruses infecting P. globosa and other phytoplankton, DNA polymerase gene (pol) fragments were amplified and the inferred amino acid sequences were phylogenetically analyzed. The results demonstrated that viruses infecting P. globosa formed a closely related monophyletic group within the family Phycodnaviridae, with at least 96.9% similarity to each other. The sequences grouped most closely with others from viruses that infect the prymnesiophyte algae Chrysochromulina brevifilum and Chrysochromulina strobilus. Whether the P. globosa viruses belong to the genus Prymnesiovirus or form a separate group needs further study. Our data suggest that, like their phytoplankton hosts, the Chrysochromulina and Phaeocystis viruses share a common ancestor and that these prymnesioviruses and their algal host have coevolved.